Rapid point‐of‐care identification of oral medications in gastric lavage content by ambient mass spectrometry in the emergency room. (26th April 2016) - Lee, Chi‐Wei; Su, Hung; Wu, Kun‐Da; Shiea, Jentaie; Wu, Deng‐Chyang; Chen, Bai‐Hsiun; Shin, Shyi‐Jang
Abstract : Rationale: Acute poisoning should be handled with high efficiency in order to minimize morbidity and mortality in the emergency room. Unfortunately, history‐taking and physical examination are not always reliable. Mis‐swallowing of oral medications is common in the pediatric group. This study aimed at developing a rapid point‐of‐care ambient mass spectrometric method for the early identification of ingested oral medications in gastric lavage content. Methods: Four different types of oral medications that are most commonly mis‐swallowed by children were diluted to different concentrations. Each of these chemical solutions was mixed with human gastric lavage content. A direct metallic sampling probe was dipped into the solution. It was then inserted promptly into the thermal desorption electrospray ionization source to carry out ionization and subsequent mass spectrometric analysis of the medications. The corresponding compounds were identified through matching of the obtained mass spectrometric data with those provided by well‐established databases. Results: Since no pretreatment of the specimen was required, the sampling step, and the subsequent thermal desorption electrospray ionization and mass spectrometric detection of the medications were completed within 30 s. Mass spectra were obtained for four different kinds of oral medication. The limit‐of‐detection of the four tested oral medications in gastric lavage content is at sub‐ppm level, which is sensitive enough for emergency medicine applications since the quantities of medications ingested by pediatric patients are usually much higher. Conclusions: Thermal desorption electrospray ionization mass spectrometry, with informational support provided by an online mass spectral database, allows for early point‐of‐care identification of mis‐swallowed oral medications in the evacuated gastric lavage contents obtained from gastric lavage of patients in the emergency room, and it is promising in providing important toxicological information to ensure the appropriateness of the subsequent medical management. Copyright © 2016 John Wiley & Sons, Ltd.